Industry 4.0: Eyeing The Future via Simulation - Aisyah, Ibrahim; Tuty Asmawaty, Abdul Kadir; Adzhar, Kamaludin (IOP Publishing, 2020)
Industry 4.0 is a future agenda. Currently, Industry 4.0 has paved the way in many industries around the world. Many initiatives have been put forward and assessed to ensure Industry 4.0 is becoming a reality. Although widely discussed in the both academic literatures and industrial publications, Industry 4.0 is encapsulated with many terms since it's inception. Some of the terms are not self-explained and often overlapped or even contradicted with similar terms in different perspectives. To demystify the issue, this paper begins with a brief overview of Industry 4.0 background including its importance and readiness. It reviews not only the technological concept with the support of nine pillars of prominent technologies, but also including the human resources as the driver behind the Industry 4.0. Dedicated section on how simulations can contribute to Industry 4.0 in ways where simulation applications can be combined with each Industry 4.0 pillars, including human resources are also presented. This paper is written in general view of Industry 4.0 so that it is easier to relate with not only with manufacturing sectors (which where Industry 4.0 was originally intended for) but also with other sectors.